Effect of digestive ripening agent on nanoparticle size in the digestive ripening process - Sahu, Puspanjali; Bhagavatula L. V. Prasad (Chemical Physics Letters, 2012)
Digestive ripening is an efficient method that leads to monodispersed nanoparticles from polydispersed ones. A systematic investigation of digestive ripening with different agents viz. dodecanethiol and dodecylamine on different metallic systems is presented. It is shown that both the metallic system involved and the digestive ripening agent have influences on the final size distribution. Further, it is demonstrated that the interaction strength between the different metals and the digestive ripening agents based on Hard Soft Acid Base principles could be invoked to explain the variation in nanoparticle size. (C) 2012 Elsevier B.V. All rights reserved.